Research Trends About Education for Sustainable Development (ESD) in Science Learning: A Bibliometric Analysis During 2014-2024 - Entang, Entang; Utama, Judhistira Aria; Liliawati, Winny; Sohn, Jungjoo; Wahyudi, Ismu (Jurnal Pendidikan MIPA, 2024)
Education for Sustainable Development (ESD) has become a critical focus in science learning as it addresses global challenges such as climate change, sustainability awareness, and resource management. However, research on ESD in science education lacks a cohesive understanding of its thematic trends, global contributions, and the role of educators. This study aims to analyze the research landscape of ESD in science learning, identify dominant thematic trends, determine leading countries in publications, and emphasize the importance of teacher understanding in implementing ESD. A bibliometric analysis was conducted using the Scopus database, with data retrieved on May 17, 2024, using the keywords “ESD in Science Learning.” The study analyzed 79 publications from 2014 to 2024, including journal articles, conference papers, reviews, and proceedings. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework was applied to screen and organize the data. Bibliometric mapping with VOSviewer revealed key thematic trends, including sustainability education, climate change, collaborative learning, and innovation in teaching. Results indicate that most research originates from developed countries, with social sciences and environmental science as the dominant subject areas. Additionally, findings highlight the urgent need for teacher capacity building to effectively integrate ESD principles into science curricula. In conclusion, this study provides a comprehensive overview of ESD research in science learning, identifies gaps, and highlights opportunities for future research and teacher training to promote sustainable development goals (SDGs).        Keywords: education for sustainable development, science learning, bibliometric analysis, PRISMA.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1317-1328